(untitled) (Forum Theologicum Sardicense, 2025)
The term "intertextuality" was introduced in the 1960s by Julia Kristeva during a period of intense literary discussion. However, the methodology of transcending the verbal, formal, and structural features of texts can be traced back to Jewish and early Christian exegetical works. Kristeva’s contribution in the 20th century was a revision and formalization of these earlier methods.